Ag@MoS2 core-shell heterostructure as SERS platform to reveal the hydrogen evolution active sites of single-layer MoS2 - Chen, Junze (2020)
Understanding the reaction mechanism for the catalytic process is essential to the rational design and synthesis of highly efficient catalysts. MoS2 has been reported to be an efficient catalyst toward the electrochemical hydrogen evolution reaction (HER), but it still lacks direct experimental evidence to reveal the mechanism for MoS2-catalyzed electrochemical HER process at the atomic level. In this work, we develop a wet-chemical synthetic method to prepare the single-layer MoS2-coated polyhedral Ag core-shell heterostructure (Ag@MoS2) with tunable sizes as efficient catalysts for the electrochemical HER. The Ag@MoS2 core-shell heterostructures are used as ideal platforms for the real-time surface-enhanced Raman spectroscopy (SERS) study owing to the strong electromagnetic field generated in the plasmonic Ag core. The in situ SERS results provide solid Raman spectroscopic evidence proving the S-H bonding formation on the MoS2 surface during the HER process, suggesting that the S atom of MoS2 is the catalytic active site for the electrochemical HER. It paves the way on the design and synthesis of heterostructures for exploring their catalytic mechanism at atomic level based on the in situ SERS measurement.